ENHANCING THESIS COMPLETION MOTIVATION IN NURSING STUDENT THROUGH SUPPORTIVE GROUP THERAPY - Wibowo, Nurhakim Yudhi; Muryani, Susi; Widhiastuti, Ratna; Khodijah; Kumala Dewi, Novi Aprilia; Widyantoro, Wisnu (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: One of the most common forms of anxiety among final-year students is thesis-related anxiety. A thesis is a requirement for students to earn their degree in their field of study. Difficulties in completing a thesis often arise from challenges in choosing a topic, writing the thesis report, and anxiety when dealing with academic advisors. This study aims to analyze the impact of social support through supportive group therapy on students' motivation to complete their thesis. Method: This study employs a one-group pre-test post-test design. The population consists of all final-year nursing students, totaling 94 students, with the sampling technique using total sampling. The therapy sessions were conducted in 14 groups, each facilitated by a supervising lecturer as a therapy facilitator. A motivation questionnaire was administered before and after the supportive group therapy sessions. The questionnaire consisted of 20 items related to motivation. Data analysis was conducted using the Wilcoxon Signed Rank Test. Results: The results of the study indicate a change in students' motivation to complete their thesis. Before the therapy, 82% of students had a moderate level of motivation, while 18% had a high level of motivation. After the therapy, the percentage of students with moderate motivation decreased to 5%, while those with high motivation increased to 95%. The data analysis showed a p-value of 0.000, which is less than 0.05. Conclusions: Supportive group therapy provides for students to share experiences and strategies for completing their thesis. Students receive emotional and social support from their peers and facilitators, which boosts their confidence and motivation to overcome challenges in the thesis-writing process.